Anatomical location and culture of equine corneal epithelial stem cells. (28th May 2013) - Moriyama, Hidekazu; Kasashima, Yoshinori; Kuwano, Atsutoshi; Wada, Shinya
Abstract Objective To identify morphologically the locations of equine corneal epithelial stem cells (CESCs) and to culture these cells. Animals studied We studied the eyes of 12 adult thoroughbred horses. Procedures Eye tissues were immunostained for two positive stem cell markers (p63, CK14) and one negative marker (CK3) to identify the locations of CESCs, so we could compare their immunostaining patterns with those of human stem cells previously reported. We compared the proliferation rates and morphological features of epithelial cells isolated from the corneal limbus and central cornea. Results Undifferentiated cells expressing the same immunostaining pattern as human CESCs were present in the equine corneal limbus. Cultured epithelial cells isolated from the limbus expressed the same immunostaining pattern that CESCs show histologically, but cells isolated from the central cornea did not proliferate and could not be evaluated. Conclusions Equine CESCs were localized in the epithelial basal layer of the corneal limbus, where melanocytes reside. They could be cultured without loss of their undifferentiated nature. When collecting such stem cells, it may be useful to harvest and culture corneal epithelial tissues in the limbus where melanocytes serve as an indicator of the collecting area.